The position of the Islamic community in Moravian Banovina - Velojić Dalibor Z. (Baština)
Although small in number, the Islamic religion in the territory of the Moravian Banovina remained compact and maintained strong ties with Muslims in other parts of Yugoslavia. Most of the Muslim population was concentrated in Lab and Vučitren counties, but given the administrative division of the country, it was isolated from other Albanians. The problems that were solved in this period concerned religious teaching and the construction of mosques. In terms of teaching, the Islamic community financed religious schools, the most important of which is in Nis, with, according to data, 141 students. Religious teaching in primary schools was a problem, since the Islamic community had no authority over the delivery of religious education, so it had to intervene ad hoc in case of possible benefits for Muslim children. There were no major activities among Muslims considering their small number.